Housing rental availability index: A tool for addressing supply-demand challenges in rental markets - Derkacz, Arkadiusz J.; Cohen, Viktorija (International Journal of Strategic Property Management, 2025)
We develop a Housing Rental Availability Index (HRAI) to measure rental housing availability across Poland by incorporating household income, rental prices, and supply-side factors. The HRAI is constructed using the structured parametric approach, offering a comprehensive and adaptable framework for analysing rental housing dynamics in Poland. Based on the Polish rental market data from 2021 to 2024, the HRAI reveals that supply constraints and rent fluctuations have a greater impact on rental availability than household income. This result challenges traditional affordability metrics. Sensitivity analysis confirms that rental availability emerges from the interaction of supply and demand rather than from either factor alone. This integrated approach positions HRAI as an “anti-separatist” indicator and presents an original approach to examining rental housing availability. The index can help local and national policymakers design targeted rent subsidies, address supply-demand imbalances, and promote spatial equity. Our findings highlight the value of combining economic measures into a single availability index and provide a framework for applying the HRAI in both academic research and housing policy decisions.